Burden and Risk Factors of Diabetic Retinopathy Among Diabetic Patients Attending a Multispecialty Tertiary Eye Hospital in Nepal - Shrestha, Arjun; Suwal, Rinkal; Shrestha, Rajan; Khadka, Deepak (Nepalese Journal of Ophthalmology, 2022)
Introduction: As the number of people with diabetes mellitus is increasing because of urbanization and change in dietary habits and sedentary lifestyle, the number of diabetic retinopathy is also expected to increase in future. [1] [sa2] We aimed to find out the prevalence of diabetic retinopathy and associated risk factors among diabetic patients in the tertiary eye hospital. Materials and methods: This is the observational cross-sectional study enrolling 420 diabetic patients visiting the multispecialty tertiary eye hospital between March 2020 and February 2021. Anthropometry measurement, laboratory risk profiles and blood pressure were recorded Results: The prevalence of any diabetic retinopathy, proliferative diabetic retinopathy, and diabetic macular edema were 30.96 %, 6.19 %, and 5.95 % respectively. The duration of DM (p=0.001), hypertension (p=0.04), high SBP (p=0.023), abdominal obesity (p=0.015), high LDL(p=0.011) cholesterol, low HDL cholesterol(p=0.012), and creatinine (p=0.001) were associated with DR in our study. Conclusion: A holistic approach should target to control the modifiable risk factors like blood sugar, blood pressure, lipid profile, kidney function, and obesity to prevent DR. Anthropometric assessment of waist to height and waist circumference should be included in the holistic health promotion strategy in Nepal as BMI may not be risk factors for DR in Nepalese people.